Potential Impact of Fulfilment of Minimum Essential Force (MEF) to The Regional Welfare - Haryanto, Joko Tri (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 1, Februari 2017 (pp. 1 - 107)DO - 10.24843/JEKT.2017.v10.i01.p04, 2017)
As with other aspects, the element of meeting the needs of national defence and security becomes very crucial aspect. These elements are not only coming from the domestic, but also related to the system of inter-state relations. To ensure the creation of the defence system and optimal security, policy will require minimum essential forces (MEF), which will outline the major components of the minimum requirements of national defence should be prepared to face any threats. The fulfilment of MEF must also provide welfare impacts for the region. For this reason this study was conducted with the purpose of calculating the impact of compliance with the MEF on the welfare of the region, especially in West Java province. IRIO using spatial approach, it can be concluded that the domestic defence industry is projected to have a role that is quite high, especially for the regional economy. To the West Java region, industrial goods of metal, in which there is the defence industry, encourage the creation of outputs and increase the income of workers. Although most of the economy and its impact enjoyed by workers in the territory, region or other provinces also continue to enjoy the effects of the increase in output and labour income.
Keywords: MEF, IRIO, National Defense System